PERCEPÇÃO DA COMUNIDADE DE AQUIDAUANA-MS QUANTO A RELAÇÃO ENTRE QUALIDADE DE PRODUTOS CÁRNEOS E BEM-ESTAR ANIMAL - Escobar, Loraine; Mendes, Dalton; Avalhaes, Vande Roberto; Pereira, Hugo; Piazzon, Cleiton José; Correia, Aline (ANAIS DO ENIC, 2018)
-